Sprint mechanical properties of professional soccer players during a match simulation - Huthöfer, M.; Harbour, E.; Schwameder, H.; Kröll, J. (ISBS Proceedings Archive (Michigan), 2020)
The purpose of this study was to identify soccer-specific changes of mechanical properties in sprinting during a simulated soccer match. Professional soccer players (n=15) completed six sprint measurements before, during and after a simulated soccer game (i.e. Copenhagen Soccer Test). Mechanical properties (theoretical maximal sprinting velocity (V0), theoretical maximal horizontal force (F0), maximal horizontal sprinting power (Pmax) and the 20-metre sprint time were computed from continuous velocity data captured from a laser device. The results suggest that soccer-specific fatigue affects V0 more than F0. Furthermore, there is an inactivity-induced sprint performance loss because of the half-time break. However, at the end of the game, professional players can achieve similar sprint times as in the first half. These results could be useful for effective training planning and optimizing sprint performance during a match.